Types of lithofacies in the Lower Cambrian marine shale of the Northern Guizhou Region and their suitability for shale gas exploration - Lingyun Zhao; Peng Xia; Yong Fu; Ke Wang; Yuliang Mou (Natural Gas Industry B)
The lithofacies and thermal maturity of the over-mature Lower Cambrian marine shale in the Northern Guizhou Region, and their impacts on reservoir properties in this shale were analyzed by combining geochemistry, mineralogy, and gas adsorption methods. Ten lithofacies were identified, and the dominant lithofacies in the studied shale are lean-total organic carbon (TOC) argillaceous-rich siliceous shale (LTAS), medium-TOC siliceous shale (MTSS), and rich-TOC siliceous shale (RTSS). Since the gas generation potential of organic matter was weak, meso- and macro-pores were compressed or filled during the thermal evolution stage with a vitrinite reflectance (RO) range of 3.0%–4.0%. The controlling factors for methane adsorption capacity in the shale samples are significantly influenced by TOC content rather than thermal maturity. Among the RTSS, MTSS, and LTAS samples, RTSS exhibits the highest favorability for preserving hydrocarbon gas, followed by MTSS. The shale types in this study play a significant role in determining the properties of shale reservoirs, serving as an effective parameter for evaluating shale gas development potential. The RTSS and MTSS with a RO range of 2.0%–3.0% stand out as the most favorable target shale types for shale gas exploration and development.